Reproductive health education model for university students utilizing social media channels: Designing and testing - Wulandari, Respati; Aprianti, Aprianti; Mubarokah, Kismi; Anggraini, Fitria Dewi Puspita (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Background: Adolescent growth encompasses physical, biological, psychological, and social aspects, including interest in the opposite sex. Providing information and support related to reproductive health helps adolescents make proper and safe decisions. Objectives: This study aims to design and validate a reproductive health education model for university students.Methods: The study is a mixed method with a multi-stage design using the 4-phase Research and Development design approach (need assessment, model development, implementation, expert validation, and final product). This research involved 221 university students (online survey), 5 managers of adolescent education programs, 6 university students (in-depth interviews), and 10 peer educators (Focus Group Discussion). Data analysis was descriptive and content analysis.Results: The generated reproductive health education model consists of 1)educators (competent, trustworthy, peer, young, survivors, and good-looking), 2)recipients (late adolescents), 3)education methods (two-way, private, repetitive,), 4)education media (social media platforms), 5) educational content (all topics needed by late adolescents), 6)duration (30 seconds/topic), and 7)goals (to increase knowledge, attitudes, and behaviors regarding reproductive health among university students). Expert validity testing: the model was highly accepted and deemed suitable for implementation (94.7%).Conclusion: The educational model developed is encouraged for implementation among university students. Introducing and implementing the model requires support from relevant stakeholders (NGOs, students, faculty, and university stakeholders). Implementation is necessary to prove the model's effectiveness in increasing knowledge, attitudes, and behaviors regarding reproductive health among university students.